Вивчення сучасного стану сформованості компетентності провізорів з надання першої долікарської допомоги - Омельчук, Михайло; Omelchuk, Mykhailo (Східноєвропейський національний університет імені Лесі Українки, 2016)
У запропонованій статті розглянуто питання компетентності провізорів з надання першої долікарської допомоги, проведена оцінка рівня теоретичних знань та практичних навичок. Запропоновано план заходів щодо покращення компетентності з її надання у майбутніх провізорів під час проходження циклу «Допомога при невідкладних станах та гострих отруєннях» як складової навчального плану післядипломного навчання. The proposed article the question of competence of pharmacists to provide first aid, and by analyzing anonymous survey of 144 pharmacists future assessed the level of theoretical knowledge and practical skills. The attention is focused on the relevance and necessity of mastering the knowledge and skills of basic resuscitation (BLS) and rapid use of automated external defibrillator (AED), as activities that significantly affect survival in stopping blood flow. The survey results show the lack of motivation to study, and a low level of knowledge in providing first aid in future pharmacists. An action plan is offered to improve the competence to provide first aid for future pharmacists during their cycle "Assistance in emergency conditions and acute poisoning" as part of the curriculum of postgraduate studies, namely - the use of methods of active and interactive learning through simulation scenarios; method of four steps and the method of continuous assessment.
The study of the current state of formation of pharmacists competence to provide first aid
Keywords: автоматичний зовнішній дефібрилятор; базові реанімаційні заходи; компетентність з надання першої долікарської допомоги; automatic external defibrillator; basic resuscitation; competence to provide first aid